PARTISIPASI ANGGOTA DALAM MENINGKATKAN KEMAMPUAN KELOMPOK TANI DI KELURAHAN EKA MARGA, LUBUK LINGGAU - Lukman Effendy; Thopan Thopan (Politeknik Pembangunan Pertanian Bogor, 2020)
The research about member’s participation to increase farmer group ability, has been done at farmer group in Eka Marga sub-district, Lubuk Linggau. The aim of this research is to know members participation level to increase group ability and function. Collecting data uses questionnaire with direct interview technique decides 57 person as respondents from six farmers groups. Descriptif Analisys and statistical analisys konkordasi kendall W uses in this researh. The result showed that level of member’s participation to increase group ability is lowest especialy for decision making. The ability of members to carry out group function is midle average. Group members ability is lowest to carry out production unit and learn class group function.